Os jogos eletrônicos de realidade aumentada na perspectiva dos três momentos pedagógicos - Fior, Greici (2022)
The present study presents as the theme the Electronic Games of Augmented Reality in the context of Physical Education, from the dynamics of the Three Pedagogical Moments proposed by Delizoicov, Angotti and Pernambuco. Since the insertion of Electronic Games has been required in the current legislation applicable in the Brazilian educational environment, and is increasingly present in our society and in the daily lives of our students, this study has led to the following questioning: How Augmented Reality Electronic Games may be present as learning practices that contribute to the body performance, through an organized methodology according to the Three Pedagogical Moments to be inserted in the area in Physical Education? In order to address this issue, the general objective of this investigation was to check the potential that the use of Electronic Games can promote in pedagogical practice for the teaching of motor skills, though applications of Augmented Reality in Physical Education classes, in a context where the need arises to seek possibilities of action in the face of this reality of, without causing absence of movement, in front of a reality that alerts us to the damage caused by such a lack. In relation of the methodological path, this is a qualitative research, through a Didactic Sequence proposed as educational product entitled Technology in Court: Augmented Reality Games in Physical Education School. Since we experienced the complicated current moment of the Covid-19 Pandemic that brought up the need for several adaptations, then the Didactic Sequence was analyzed, through questionnaires and semi-structured interviews, by seven Physical Education teachers from the State Educational System of Rio Grande do Sul and the Municipal Educational System Educational System of Passo Fundo, and to evaluate its potential was offered an on line extension course to teachers in order to support them to evaluate the applicability of Educational Product. The results showed that the activities and methodologies available in the educational product are considered adequate to assist the teacher´s teaching in their classes, and also contribute significantly to the promotion of students´ learning in Physical Education classes. The results showed that the activities and methodologies available in the referred Educational Product are considered adequate to assist the teacher´s teaching in their classes, making classes more interesting and attractive, improving this way the teaching-learning practice and also contributing significantly to the promotion of students´ learning in Physical Education classes. Finally, the study points out the need to share the strategies of this Educational Product, so in the context of Physical Education, it is an innovative study based on the dynamics of 3MP and an Education Product geared at this curricular component, that they are available to teachers so that they can implement them in their teaching practices. It is also emphasized that this dissertation is accompanied by the Educational Product available at: <http://educapes.capes.gov.br/handle/capes/716737>.